Automatic Defect Detection System For Leadframe Inspection - Rajamony, Bhuvanesh Abhinesh (2004)

(untitled)
Defect detection and classification are important for both product quality assurance and process improvement in the maimfacturing industry. Machine vision systems offer several beneficial. features such as consistency, accuracy and round the clock repeatability. This thesis presents the results of the development and implementation of such a machine vision system to automate the inspection of leadframes.